The structure of (E)-6-(cyclopropylmethyl)-11-(2,2-difluoropropylidene)-2-methyl-6, 11-dihydrodibenzo[c,f][1,2]thiazepine 5,5-dioxide, C21H21F2NO2S - Wang Ji; Wu Wenhui; Lin Fuhua; Wang Jie; Zhang Xiuzhi (Zeitschrift für Kristallographie - New Crystal Structures, 2025)
C21H21F2NO2S, monoclinic, P21/n (no. 14), a = 12.0799(4) Å, b = 12.8538(4) Å, c = 12.2063(4) Å, β = 95.769(1)°, V = 1885.70(11) Å3, Z = 4, R gt(F) = 0.0437, wRref (F 2) = 0.1261, T = 150 K.